APPLICATION OF PROBLEM BASED LEARNING MODEL TO INCREASE ANALYZE SKILL PHYSICS PROBLEMS OF STUDENTS IN CLASS XI IPA OF SENIOR HIGH SCHOOL - Harika Wulan Sari; Zuhdi Ma'aruf; Mitri Irianti (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
The research aimed to know the differences in the analyze skill students physics problems applying the problem based learning model with the conventional learning. The research method used was quasy experiment with posttest only control design. The subject is class XI IPA which consists of 4 classes. Samples of two classes selected by simple random sampling, obtained class XI IPA4, amounting to 32 students as an experimental class and class XI IPA3, amounting to 33 students as a control class. Research instrument use is about a test analyze skills physic problems given to students after the learning process is caried out in two classes. Data analysis techniques used in this study are descriptive analysis and inferential analysis. The results showed the there are significant differences in the analyze skill students physic problems between the class applying the problem based learning model and the class applying conventional learning on optical geometry. Analyze skills of class experiment score of average higher than class control apply conventional learning. Therefore application problem based learning model can increase analyze skill students physics problems.